Forward with Patton : The World War II Diary of Colonel Robert S. Allen - Allen, Robert S. (Robert Sharon), 1900-1981 (Book collections on Project MUSE., 2017)
Soldier, journalist, and Soviet spy Robert S. Allen (1900--1981) was a deeply controversial figure. After serving in France during World War I, he left the military, forged a successful career as a syndicated columnist, and even rose to become the Washington, DC, bureau chief for the Christian Science Monitor. During this period, he developed a sideline as a paid informant for the KGB. Still, Allen returned to the army following America's entry into World War II and served as General George S. Patton's chief of situation and executive officer for operations. He was considered such an authority on Patton after the war that Twentieth Century-Fox asked him to develop a film script about the general. In Forward with Patton, John Nelson Rickard presents a complete, annotated edition of Colonel Allen's World War II diary for 1944-1945. The entries reflect Allen's private thoughts on his experiences, provide insight into the employment of the Third Army staff, and survey the strengths and weaknesses of individual staff members. They also provide an invaluable and rare perspective of Patton, with whom Allen worked closely while gathering intelligence, and whom he deeply admired. At times objective and at others intensely personal, Forward with Patton offers a distinctive eyewitness account of one of the US military's most important armies by one of its most colorful soldiers.